Understanding S-shaped current-voltage characteristics of organic solar cells: direct measurement of potential distributions by scanning Kelvin probe - Saive, Rebecca; Müller, Christian; Schinke, Janusz; Lovrinčić, Robert; Kowalsky, Wolfgang (Applied physics letters, 2013)
We present a comparison of the potential distribution along the cross section of bilayer poly(3-hexylthiophene)/1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]C61 (P3HT/PCBM) solar cells, which show normal and anomalous, S-shaped current-voltage (IV) characteristics. We expose the cross sections of the devices with a focussed ion beam and measure them with scanning Kelvin probe microscopy. We find that in the case of S-shaped IV-characteristics, there is a huge potential drop at the PCBM/Al top contact, which does not occur in solar cells with normal IV-characteristics. This behavior confirms the assumption that S-shaped curves are caused by hindered charge transport at interfaces.
Gesehen am 26.01.2022